Synthesis of Unsaturated Nonionic Poly(ester‐sulfones) via Acyclic Diene Metathesis (ADMET) Polymerization and Anode‐Selective Electrophoretic Deposition. Issue 23 (26th September 2016) - Kawarazaki, Isamu; Takasu, Akinori
Abstract : Nonionic aliphatic polymers containing ester and sulfonyl moieties, [poly(ester‐sulfones)s] were found to undergo anode‐selective electrophoresis under electrophoretic deposition conditions. Herein are reported the syntheses of unsaturated nonionic polyesters containing sulfide linkages and double bonds on the polymer backbone via acyclic diene metathesis polymerization using a Grubbs' catalyst. Subsequent oxone oxidation was carried out, affording the corresponding poly(ester‐sulfone), followed by electrophoretic deposition of the unsaturated poly(ester‐sulfone) onto stainless steel. Subsequent UV‐irradiation cured the deposited film, improving the peeling strength of the coating. Abstract : Synthesis of nonionic unsaturated poly(ester‐sulfones) via ADMET polymerization and anode‐selective electrophoretic deposition.